Does anti‐tumor necrosis factor alpha prevent the recurrence of Crohn's disease? Systematic review and meta‐analysis. Issue 4 (14th October 2020) - Uchino, Motoi; Ikeuchi, Hiroki; Hata, Keisuke; Minagawa, Tomohiro; Horio, Yuki; Kuwahara, Ryuichi; Nakamura, Shiro; Watanabe, Kenji; Saruta, Masayuki; Fujii, Toshimitsu; Kobayashi, Taku; Sugimoto, Ken; et al.
Abstract: Background and Aim: Anti‐tumor necrosis factor (TNF) α agents are now well known to function as effective treatments for Crohn's disease (CD). Several meta‐analyses have revealed the efficacy of anti‐TNF therapy for preventing recurrence after surgery; however, the efficacies reported in some prospective studies differed according to the outcomes. Moreover, adverse events (AEs) were not well evaluated. We conducted this systematic review and meta‐analysis to evaluate both the efficacy of anti‐TNF therapy after stratification by the outcome of interest and the AEs. Methods: We performed a systematic literature review of studies investigating anti‐TNF therapy, CD, and postoperative recurrence. Meta‐analyses were performed for endoscopic and clinical recurrence and AEs. Results: A total of 570 participants, including 254 patients in the intervention group and 316 patients in the control group, in eight studies, were analyzed for recurrence. Based on the results of the meta‐analysis, the efficacies of anti‐TNF therapy at preventing endoscopic and clinical recurrence were as follows: relative risk (RR) 0.34, 95% confidence interval (CI) 0.22–0.53 and RR 0.60, 95% CI 0.36–1.02, respectively. The RR of AEs with anti‐TNF therapy was 1.75 (95% CI 0.81–3.79). Conclusions: Anti‐TNF therapy after surgery for CD displays efficacy at preventing endoscopic recurrence for 1–2 years, without increasing the incidence of AEs. However, clinical recurrence was not significantly reduced. The efficacy of postoperative anti‐TNF therapy may differ in terms of the outcomes, which include long‐term prevention, the avoidance of further surgery, and cost‐effectiveness.